2013
DOI: 10.1128/mcb.00688-13
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of p38 Mitogen-Activated Protein Kinase in Multiple Sclerosis and Its Models

Abstract: Multiple sclerosis (MS), the most common disabling neurologic disease of young adults, is considered a classical T cell-mediated disease and is characterized by demyelination, axonal damage, and progressive neurological dysfunction. The currently available disease-modifying therapies are limited in their efficacy, and improved understanding of new pathways contributing to disease pathogenesis could reveal additional novel therapeutic targets. The p38 mitogen-activated protein kinase (MAPK) signaling pathway is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
61
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(72 citation statements)
references
References 74 publications
3
61
0
2
Order By: Relevance
“…Generation and amplification of TNF-a and IL-1b have been reported to be regulated by NF-jB p65 [26][27][28]. In addition to NF-jB p65 signaling, MAPKs are also important signaling molecules involved in the production of pro-inflammatory mediators and cytokines and the modulation of NF-jB p65 in microglia [29,30]. One of the MAPK families, p38, is related to LPS signaling in microglial cells, which respond to pro-inflammatory cytokines [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Generation and amplification of TNF-a and IL-1b have been reported to be regulated by NF-jB p65 [26][27][28]. In addition to NF-jB p65 signaling, MAPKs are also important signaling molecules involved in the production of pro-inflammatory mediators and cytokines and the modulation of NF-jB p65 in microglia [29,30]. One of the MAPK families, p38, is related to LPS signaling in microglial cells, which respond to pro-inflammatory cytokines [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…P38 MAPK (p38) is a member of the MAPK family and is centrally involved in diverse cellular processes, including inflammation, cell differentiation, cell growth and cell death 19. A wealth of data has indicated that p38 is also a key regulator in multiple renal diseases 20.…”
Section: Introductionmentioning
confidence: 99%
“…NF-κB binds to the DNA and its transcriptional activity regulates several genes, which promote neuroinflammation. The p38 mitogenactivated protein kinase (p38 MAPK) signalling pathway also plays an important role in the expression and activity of pro-inflammatory cytokines in microglial cells [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…NF-κB binds to the DNA and its transcriptional activity regulates several genes, which promote neuroinflammation. The p38 mitogenactivated protein kinase (p38 MAPK) signalling pathway also plays an important role in the expression and activity of pro-inflammatory cytokines in microglial cells [6][7][8].Excessive production of pro-inflammatory mediators generated during neuroinflammation can damage neighbouring neurons, and further activate the microglia, as well as other glia cells resulting in a self-perpetuating cycle [2,4,9].Furthermore, activation of the microglia and the resulting neuroinflammation play a critical role in the pathogenesis of neurodegenerative disorders such as Alzheimer's disease (AD) [10]. Consequently, pharmacological modulation of pro-inflammatory mediators generated by the microglia during chronic inflammation and modulation of the signalling pathways responsible for their production is an important target in treating severe neuroinflammatory disorders.…”
mentioning
confidence: 99%